MRI-Based Pancreatic Atrophy Is Associated With Malignancy or Invasive Carcinoma in Intraductal Papillary Mucinous Neoplasm - Lin, Tingting; Chen, Xin; Liu, Jingjing; Cao, Yingying; Cui, Wenjing; Wang, Zhongqiu; Wang, Cheng; Chen, Xiao (Frontiers in Oncology, 2022)
Background: Abrupt change in caliber of main pancreatic duct (MPD) with distal pancreatic atrophy (PA) was considered as one of worrisome features in International Association of Pancreatology guideline and American College of Gastroenterology guideline for the management of intraductal papillary mucinous neoplasms (IPMNs). However, this feature was not included in other guidelines. Moreover, the association between PA alone and malignancy in IPMNs has not been fully evaluated. In the present study we investigated the role of image-based PA in identifying malignant IPMNs or invasive carcinoma. Methods: A total of 186 patients with IPMNs were included for analysis. Tumor size, location, MPD diameter, presence of mural nodule (MN) and PA were evaluated using magnetic resonance imaging. Demographic information and serum carbohydrate antigen 19-9 (CA19-9) and carcinoembryonic antigen (CEA) levels were also collected. IPMNs with high grade dysplasia and associated invasive carcinoma were regarded as malignant IPMNs. Results: PA was observed in 34 cases (18.3%). The occurrence of malignant IPMNs or invasive carcinoma in patients with PA were significantly higher than in those without PA (52.9% vs 22.3%; 44.1% vs 8.9%, all P < 0.01). Multivariate logistic regression analysis showed that PA was an independent associated factor for malignant IPMNs (odds ratio (OR) = 2.69, 95% confidence interval (CI): 1.07-6.78) or invasive carcinoma (OR = 7.78, 95%CI: 2.62-23.10) after modified with confounders. Subgroup analysis in MPD-involved IPMNs also indicated that PA was an independent associated factor for invasive carcinoma (OR = 9.72, 95%CI: 2.43-38.88). PA had similar performance with MPD plus MN (the area under the curve (AUC) both was 0.71) in identifying malignancy. PA had a higher performance in identifying invasive carcinoma in MPD-involved IPMNs than MN (AUC = 0.71 vs 0.65, P = 0.02). Conclusion: Our data showed that imaging-based PA was associated with malignancy or invasive carcinoma regardless of abrupt change in caliber of MPD in IPMNs. PA had acceptable performance in identifying malignant IPMNs.